2016
DOI: 10.1007/s11011-016-9797-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of serum cholesterol are associated with better performance on tasks of episodic memory

Abstract: Objective We examined how serum cholesterol, an established risk factor for cerebrovascular disease (CVD), relates to cognitive function in healthy middle-older aged individuals with no neurologic or CVD history. Method A complete lipid panel was obtained from a cohort of one hundred twenty individuals, ages 43–85, who also underwent a comprehensive neuropsychological examination. In order to reduce the number of variables and empirically identify broad cognitive domains, scores from neuropsychological tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…However, higher LDL-C levels have also been reported to be positively associated with better memory function. It may be due to the fact that LDL-C may negatively be associated with AD only when the increase lasts for a long enough duration (Leritz et al, 2016). Therefore, follow-up cohort studies with a large sample size are needed to strengthen our results in this study.…”
Section: Discussionmentioning
confidence: 83%
“…However, higher LDL-C levels have also been reported to be positively associated with better memory function. It may be due to the fact that LDL-C may negatively be associated with AD only when the increase lasts for a long enough duration (Leritz et al, 2016). Therefore, follow-up cohort studies with a large sample size are needed to strengthen our results in this study.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is clear that cholesterol ranges considered risk factors for cardiovascular disease are very different than having values in normal range. It was recently reported that higher cholesterol levels are associated with better performance on memory tests in cognitively healthy middle-older adults (Leritz et al, 2016). Such higher values of blood cholesterol could even be related to a release of excessive quantities of these molecules from the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Novel animal data have demonstrated that gene knockout of the LDL receptor may be associated with hippocampal apoptosis 11. Recent human studies suggest that statin users are more likely to suffer from cognitive impairment than non-statin users,12 with impairments in executive functioning, episodic memory, and other cognitive domains associated with low LDL levels 13,14. This remains controversial, as well-designed prospective longitudinal studies and randomized controlled trials have not necessarily found an association between LDL and cognition 1517…”
Section: Introductionmentioning
confidence: 99%